Golden Visa and Foreign Investment in Islamic Banking: Legal Opportunities and Challenges in Indonesia - Ahmad Nabil Adzikri; Muhammad Arief Hamdi; Alrin Tambunan (Institut Agama Islam (IAI) SEBI, 2025)
The Golden Visa policy under Minister of Law and Human Rights Regulation Number 22 of 2023 introduces a new immigration instrument to attract long-term foreign investment through residence permits of 5–10 years. While facilitating both individual and corporate investors, including potential investment in the Islamic banking sector, this policy raises a legal synchronization issue. Under Law Number 21 of 2008 and OJK Regulation Number 16 of 2022, foreign ownership in Islamic banks may reach 99% of paid-up capital, creating potential conflicts with immigration policy and the maslahah principle in Islamic economics. This study applies normative legal research with statutory and conceptual approaches, analyzing immigration regulations, banking law, and sharia principles. Findings show that the Golden Visa offers opportunities to strengthen Islamic banking assets, expand global competitiveness, and support the halal industry. However, it also poses risks of foreign dominance, capital flight, and divergence from sharia values. Regulatory harmonization is therefore crucial to ensure that the Golden Visa contributes to sustainable economic growth while safeguarding the sovereignty of Indonesia’s Islamic financial sector.Kebijakan Visa Emas, berdasarkan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 22 Tahun 2023, memperkenalkan instrumen imigrasi baru untuk menarik investasi asing jangka panjang melalui izin tinggal 5–10 tahun. Sembari memfasilitasi investor individu dan korporasi, termasuk potensi investasi di sektor perbankan syariah, kebijakan ini menimbulkan isu sinkronisasi hukum. Berdasarkan Undang-Undang Nomor 21 Tahun 2008 dan Peraturan OJK Nomor 16 Tahun 2022, kepemilikan asing di bank syariah dapat mencapai 99% dari modal disetor, yang berpotensi menimbulkan konflik dengan kebijakan imigrasi dan prinsip maslahah dalam ekonomi Islam. Studi ini menerapkan riset hukum normatif dengan pendekatan hukum dan konseptual, menganalisis peraturan imigrasi, hukum perbankan, dan prinsip-prinsip Islam. Temuan menunjukkan bahwa Visa Emas menawarkan peluang untuk memperkuat aset perbankan syariah, memperluas daya saing global, dan mendukung industri halal. Namun, kebijakan ini juga menimbulkan risiko dominasi asing, pelarian modal, dan penyimpangan dari nilai-nilai Islam. Oleh karena itu, harmonisasi regulasi sangat penting untuk memastikan bahwa Golden Visa berkontribusi pada pertumbuhan ekonomi berkelanjutan sekaligus melindungi kedaulatan sektor keuangan Islam Indonesia.